2019
DOI: 10.2485/jhtb.28.71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dietary Supplement on Peri-Implant Bone Strength in a Rat Model of Machined Surface Implants

Abstract: Efforts to improve the bone-implant interface to accelerate and improve the quality of osseointegration have generally focused on chemically improving the interface by incorporating inorganic phases on or into the titanium oxide layer or physically improving it by increasing the level of roughness. However, some types of rough-surfaced implants, such as those coated with hydroxyapatite (HA), may result in a higher incidence of complications. Once peri-implantitis occurs, the factors promoting bone integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Watanabe et al 9) administered SBM to rats by including it in their food and found that the oral ingestion of the SBM was effective in the promotion of bone formation. Sato et al reported that, when they embedded implants that caused mechanical friction in the femurs of rats that had ingested SBM as a supplement, new bone formation was promoted in the peri-implant region 5) . Srinivasan et al reported that SBM was effective as a supplement in maintaining bone health in subjects experiencing adverse effects on their bone microstructure and bone density, such as estrogen and mineral deficiencies 6) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Watanabe et al 9) administered SBM to rats by including it in their food and found that the oral ingestion of the SBM was effective in the promotion of bone formation. Sato et al reported that, when they embedded implants that caused mechanical friction in the femurs of rats that had ingested SBM as a supplement, new bone formation was promoted in the peri-implant region 5) . Srinivasan et al reported that SBM was effective as a supplement in maintaining bone health in subjects experiencing adverse effects on their bone microstructure and bone density, such as estrogen and mineral deficiencies 6) .…”
Section: Discussionmentioning
confidence: 99%
“…A total of twenty-four Ti-6Al-4V (wt%) cylindrical implants measuring 1.2 mm in diameter and 4.0 mm in height, with a hole located 0.5 mm from the upper end for pull-out strength tests, were used. All twenty-four implants were subjected to blasting with 110-μm abrasive particles, cleaned with an ultrasonic device, and autoclaved, as per the method described by Sato et al 5) and Watanabe et al 9) . They were then subjected to ultrasonic cleaning in double-distilled water.…”
Section: Surface Treatment Of Implantsmentioning
confidence: 99%
See 1 more Smart Citation